Hungarian Monitoring, 19 December 1988 . [Magyar rádiófigyelő], 1988. december 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Shevardnadze's Tokyo talks - Pravda and TASS reports on the Armenian problems - Soviet banker on the need for Comecon financial reform and later possible devaluation of the ruble to the dollar - Party-like formation set up in Poland under Walesa's leadership - Persian Gulf summit Domestic Affairs: - "Bagoly" (Owl): radio bridge with the Hungarian department of Voice of America - Ministerial council press office holds international press conference - Popular Front national council pushes for formation of new election law - Alternative groups meeting at Vörösmarty Square demand elections for constitutional national assembly - Independent trade unions form League and start action against planned modifications of Labor Law and draft strike law - "Népszabadság" (People's Freedom) daily publishes interview with historian Bálint Szabó on Soviet leadership and relations with the Rákosi-Gerő regime Economy: - Chamber of Commerce thinks budget income could be increased with sales of state property - National Cooperatives Council urges government to make clear statement on the future of cooperatives - Frigyes Berecz at the Komárom county party committee meeting: the government acknowledges that it was a mistake to support the eocene program. He also talked about the future of miners to be laid off. - The Secreteary General of the Economic Chamber reported on the Hungarian Days in Tel Aviv Külpolitika: - Sevardnadze tokiói tárgyalásai - Pravda - És TASZSZ-beszámoló örményországi problémákról - Szovjet bankár a KGST pénzügyi viszonyainak szükséges reformjáról és a rubelnek a dollárhoz viszonyított későbbi esetleges leértékeléséről - Pártszerű képződmény alakult Lengyelországban Walesa vezetésével - Perzsa-öböl menti csúcstalálkozó Belpolitika: - "Bagoly": RÁDIÓHÍD az AMERIKA HANGJA magyar osztályával - A minisztertanács sajtóirodájának nemzetközi sajtótájékoztatója - A népfront országos tanácsa új választási törvény megalkotását szorgalmazza - A Vörösmarty téren alternatív csoportok alkotmányozó nemzetgyűlés választását követelték - A független szakszervezetek Ligába tömörültek és akciót indítanak a Munka Törvénykönyv tervezett módosítása és a készülő sztrájktörvény ellen - A Népszabadság interjút közöl Szabó Bálint történésszel a szovjet vezetés, valamint a Rákosi-Gerő-rezsim viszonyáról Gazdaság: -A Gazdasági Kamara szerint növelhető lenne a költségvetés bevétele az állami tulajdon értékesítésével - A kormány félreérthetetlenül foglaljon állást a szövetkezetek jövőjével kapcsolatban, sürgeti az Országos Szövetkezeti Tanács - Berecz Frigyes a Komárom megyei pártbizottság ülésén: a kormány elismeri, hogy hiba volt az eocén-programot támogatni. Beszélt az elbocsátandó bányászok jövőjéről is - A Gazdasági Kamara főtitkára beszámolt a tel-avivi magyar napokról